Associations with virologic treatment failure in adults on antiretroviral therapy in South Africa. - Datay, M; Boulle, A; Mant, D; Yudkin, P (2010)
OBJECTIVES: Highly active antiretroviral therapy (HAART) has been available in government facilities in the Western Cape Province of South Africa since 2001. We aimed to investigate factors associated with virologic treatment failure in this setting. DESIGN: Case-control study, matched on facility and on starting date and duration of HAART. METHODS: Cases and controls were identified from clinic registers from May 2001 to June 2006. Cases were patients who switched to second-line therapy after confirmed virologic failure (2 consecutive viral loads above 1000 copies/mL). Controls were on first-line treatment with viral load <400 copies per milliliter at the time of case incidence. RESULTS: One hundred thirty cases and 238 controls were selected from 8 clinics (median 16.6 months on HAART, interquartile range: 12.2-24.6). Treatment interruptions [adjusted odds ratio (AOR) 8.6, 95% confidence interval: 3.6 to 20.8], prior nevirapine-based prevention of mother-to-child transmission (PMTCT) treatment (AOR: 9.6, 95% confidence interval: 2.9 to 32.2), a baseline CD4 count less than 50 cells per microliter or from 50-150 cells per microliter (AOR: 6.6, 95% confidence interval: 2.3 to 18.8 and AOR: 5.8, 95% confidence interval: 2.1 to 16.3 compared with a baseline CD4 count of more than 150 cells/microL), and the use of nevirapine in the initial regimen (AOR: 2.5, 95% confidence interval: 1.4 to 4.7) were all independently associated with virologic treatment failure. CONCLUSIONS: In this setting, nevirapine in the initial HAART regimen or for PMTCT treatment is associated with virologic treatment failure, together with low CD4 count at ART initiation. Earlier initiation of HAART and access to improved triple therapy and PMTCT regimens are priorities for HIV programs in Southern Africa.